2020
DOI: 10.1021/jacs.0c10786
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Adhesion at Extremely Low Temperatures: A Combined Experimental and Theoretical Investigation

Abstract: Adhesive materials that are resistant to low temperatures have wide applications in daily life, scientific research, and industry. Currently, the overwhelming majority of low-temperature-resistant adhesives are traditional polymer systems. In this study, a new strategy was developed to obtain strong and long-lasting adhesion effects from low-molecular-weight adhesives at low temperatures. The introduction of water molecules and the formation of hydrogen bonds not only triggered supramolecular polymerization bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
92
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(100 citation statements)
references
References 55 publications
1
92
1
Order By: Relevance
“…Figure 3G shows the comparison of adhesion strength of industrial tapes and various reversible adhesives reported in literature vs.o ur IC gel adhesives.T he bar chart was the highest value for each type of adhesive.The adhesion strength of industrial tapes (Tesa JD4410, 3M S0073) is much lower than our IC gels.Inaddition, the adhesion strength of this IC gel was 1.2-3.6 times higher than that of reported reversible adhesives (eg. AZO, [4a] LMA, [16] CNT, [17] EVA-HMAs, [18] PC ether, [19] Gecko, [8a] PA , [6b, 20] HBPA, [21] TC-SA [7b] ), indicating the significant mechanical reinforcement super adhesion derived from the synergistic interface of hydrogen bonding between polymer and IC.…”
Section: Forschungsartikelmentioning
confidence: 99%
“…Figure 3G shows the comparison of adhesion strength of industrial tapes and various reversible adhesives reported in literature vs.o ur IC gel adhesives.T he bar chart was the highest value for each type of adhesive.The adhesion strength of industrial tapes (Tesa JD4410, 3M S0073) is much lower than our IC gels.Inaddition, the adhesion strength of this IC gel was 1.2-3.6 times higher than that of reported reversible adhesives (eg. AZO, [4a] LMA, [16] CNT, [17] EVA-HMAs, [18] PC ether, [19] Gecko, [8a] PA , [6b, 20] HBPA, [21] TC-SA [7b] ), indicating the significant mechanical reinforcement super adhesion derived from the synergistic interface of hydrogen bonding between polymer and IC.…”
Section: Forschungsartikelmentioning
confidence: 99%
“…Therefore, based on these results, the amorphous property and the flexibility of the wet SA (PU@PVP) at low temperature may contribute to the supercold tolerance adhesion. [ 36 ] The SA (PU@PVP) could be easily twisted and curled in liquid N 2 (−196 °C) with the maximum tensile strength of 1.6 ± 0.3 MPa and tensile strain of 6.1 ± 1.2% (Figure S17 and Movie S16, Supporting Information). In the object‐transferring demonstration, the SA (PU@PVP) patch could adhere the target (labeled with QR code) in Position 5 and transfer it to Position 1 at −80 °C refrigerator rapidly (Figure S18 and Movie S17, Supporting Information).…”
Section: Figurementioning
confidence: 99%
“…[34] Very recently, amorphous supramolecular polymer adhesives with low glass transition temperature (T g ) were developed to achieve lowtemperature resistant adhesion, such as cyclodextrin-acid-based deep eutectic supramolecular polymer [35] and pillar [5]arenecrown ether-water copolymer. [36] These successful examples encourage us to explore the supercold tolerance of the as-prepared SA (PU@PVP) by using the cold-resistant features of PVP [37] and PU. [7] First, we demonstrated the adhesion performance of the SA (PU@PVP) on fresh fruit, frozen meat package, cryotube, and metal box with cryopreserved cells (Figure 5a).…”
mentioning
confidence: 99%
“…The results proved the stability of these supramolecular adhesive hydrogels. [ 62–68 ] Therefore, hydrogels G1 , G2 , and G3 can all be assembled through the interfacial supramolecular adhesion.…”
Section: Construction Of the Information Code By Interfacial Supramolecular Adhesion Of Different Aie Hydrogelsmentioning
confidence: 99%